Therapeutic targeting de novo purine biosynthesis driven by β-catenin-dependent PPAT upregulation in hepatoblastoma - Ming Ding; Chunshuang Ma; Yanyan Lin; Houshun Fang; Yan Xu; Shuxuan Wang; Yao Chen; Jiquan Zhou; Hongxiang Gao; Yuhua Shan; Liyuan Yang; Huiying Sun; et al. (Cell Death and Disease)
Abstract De novo purine biosynthesis (DNPS) was previously shown to be aberrantly activated in many cancers. However, the activity of DNPS pathway and its underlying regulatory mechanism in hepatoblastoma (HB) remain poorly understood. Herein, we discovered that the expression of PPAT, the rate-limiting enzyme in DNPS, was markedly upregulated in HB, leading to an augmented purine flux via DNPS, thereby promoting both HB cell proliferation and migration. Furthermore, we found that activated mutant β-catenin, a dominant driver of HB, transcriptionally activated PPAT expression, hence stimulating DNPS and constituting a druggable metabolic vulnerability in HB. Consistently, pharmacological targeting using a DNPS inhibitor lometrexol or genetic repressing the enhanced DNPS markedly blocked HB progression in vitro and in vivo. Our findings suggest that HB patients harboring activated β-catenin mutations and consequent DNPS upregulation, may be treated efficaciously with DNPS enzyme inhibitors like lometrexol. These novel findings bear major therapeutic implications for targeted precision medicine of HB.